Role of the 92.5-kilodalton outer membrane protein of Campylobacter jejuni in serological reactions. - Jin, T (1988)
Outer membrane proteins from 12 strains of Campylobacter jejuni were examined by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and immunoblotting with rabbit antisera prepared against Formalin-treated cell suspensions of three of the strains. The 92.5-kilodalton protein was confirmed to be a minor outer membrane protein and exhibited serological heterogeneity. Serological specificities of the proteins, however, were found not to correlate with serotypic specificities of the strains, as demonstrated by slide agglutination tests with whole-cell suspensions. The results suggested that the 92.5-kilodalton proteins were not likely to be participating antigenic determinants in the immunological reactions that give rise to agglutination of live-cell suspensions in the slide test.